Planning, Organizing, Actuating, and Controlling as Predictors of Hospital Service Effectiveness: A Study in Aceh Province, Indonesia - Maulana Alhamdi Stivani; Nurjannah Nurjannah; Rachmad Suhanda (Heca Sentra Analitika, 2026)
Hospital service effectiveness is an important indicator of health service performance because it reflects the ability of hospitals to achieve service goals, support staff competence, and maintain work behavior that contributes to service quality. However, hospital services still face managerial challenges related to planning, coordination, service implementation, and quality control. This study aimed to analyze planning, organizing, actuating, and controlling as predictors of hospital service effectiveness at Ibnu Sina Hospital Aceh Besar, Indonesia. This study used a quantitative explanatory design with a cross-sectional approach. The study population consisted of 177 hospital employees involved in management and service delivery, including health and non-health workers. A total sampling technique was applied, and 123 complete responses were analyzed. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the measurement model and structural relationships among variables. The structural model showed that planning, organizing, actuating, and controlling simultaneously explained 54.7% of the variance in hospital service effectiveness. All four management functions had positive and significant effects on service effectiveness. Actuating was the strongest predictor, followed by controlling, organizing, and planning. These findings indicate that hospital service effectiveness is strongly influenced by the quality of service implementation and quality control mechanisms, while planning and organizing remain important foundations. Strengthening staff compliance with standard operating procedures, improving inter-unit communication, conducting routine monitoring, and implementing corrective actions are essential strategies to improve hospital service effectiveness.